ECOLOGICAL HERITAGE IN MINANGKABAU KIEH - Nasri, Daratullaila; Mulyadi, Mulyadi; Juliastuty, Dewi; Awwali, Muchlis; Danerek, Stefan (Center for Research and Development of Religious Literature and Heritage, 2022)
This article examines the form of Minangkabau people's wisdom and concern for nature and the environment through kieh 'allusion' or figurative language found in the form of mamangan (one of the traditional Minangkabau expressions) which contains ecological wisdom. Data of this study consist of kieh expressions in the form of suggestions and prohibitions. Kieh has several kinds of proverbs called petitih, pituah, pameo and mamangan. The object of the study is the kieh which is related to ecological problems and solutions. By employing descriptive-analytic method, the study focused on the concept of environmental ethics and the view of Minangkabau natural philosophy as summarized by A.A. Navis. It is found that the Minangkabau people through mamangan kieh express wisdom and concern for the environment, including nature conservation and preservation of natural resources. This form of wisdom guides Minangkabau community in interacting with the environment. The Minangkabau natural philosophy is attentive to the sustainability of natural resources and the sustainability of the Minangkabau customary system and communal tradition, such as inheritance in the form of agricultural land, fields, forests, and else. The ecological kieh expressed the environmental ethics for the Minangkabau community.